Low-dielectric and high-heat-resistance adamantane type maleimide resin as well as preparation method and application thereof
Through the structural design and reaction process of adamantane maleimide resin, the dielectric and heat resistance problems of maleimide resin in high-frequency signal transmission are solved, and low-dielectric and high-heat-resistant copper clad plates are prepared, with excellent comprehensive performance.
Patent Information
- Application Number
- CN202510493374.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2025-08-26
AI Technical Summary
The existing maleimide resins have insufficient dielectric constant and dielectric loss in high-frequency signal transmission, and the problems of solubility and brittleness have not been effectively solved, making it difficult to meet the needs of high-end PCB substrates.
A low-dielectric and high-heat resistance resin is prepared by reacting with maleic anhydride and acetic anhydride to form maleimide groups.
The excellent dielectric properties and high heat resistance of the resin are achieved, the dielectric constant and dielectric loss are reduced, and the processing window is extended. The prepared copper clad plate has high heat resistance and excellent dielectric properties.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of synthetic resins for electronic materials, in particular to a low-dielectric, high-heat-resistant adamantane-type maleimide resin and a preparation method and application thereof. Background Art
[0002] With the rapid development of communications technology, signal transmission in electronic devices is rapidly evolving toward high frequency and high speed. In the 5G communications industry, the demand for high-speed information transmission necessitates the use of high-frequency signals in terminal devices and communication servers. This shift places stricter demands on PCB substrates, requiring them to have lower dielectric constants (Dk) and dielectric loss factors (Df) to ensure that signal attenuation and distortion during transmission are effectively controlled. Furthermore, as the power and integration density of electronic device components increase, the demand for material heat resistance is heightened.
[0003] Currently, maleimide resins on the market, such as N,N-4,4'-diphenylmethane bismaleimide (BDM) and N,N-m-phenylene bismaleimide (PDM), have problems such as poor solubility, high brittleness, and difficulty in controlling processing conditions. In addition, the dielectric constant and dielectric loss are not sufficient to meet the needs of high-frequency information transmission.
[0004] In the prior art, the methods for solving the above technical problems are as follows:
[0005] First, the solubility and brittleness of bismaleimide are improved by introducing a third component, but the introduction of the third component often reduces the crosslinking density, rigidity and thermal conductivity of the resin.
[0006] Secondly, special functional groups are introduced on the basis of bismaleimide to solve problems such as solubility, brittleness, and thermal conductivity. For example, CN117946394A discloses a bismaleimide resin containing an indane condensation structure. By introducing an indane structure, the resin solves problems such as poor solubility and brittleness, while also achieving good thermal conductivity and a low dielectric constant. Although this method improves the brittleness, solubility, and processability of the maleimide resin, the dielectric constant and dielectric loss cannot fully meet the requirements of high-end PCB substrates, resulting in ineffective control of signal attenuation and distortion during transmission. Summary of the Invention
[0007] The present invention aims to overcome the deficiencies in the prior art and provide a low-dielectric, high-heat-resistant adamantane-type maleimide resin, a preparation method thereof, and an application thereof. The adamantane-type maleimide resin provided by the present invention contains a symmetrical, nearly spherical adamantane structure, which contains only carbon and hydrogen non-polar groups and can increase the free volume of the molecule, thereby imparting excellent dielectric properties to the resin and solving the problems of poor solubility and high brittleness of the maleimide resin. The adamantane-type maleimide resin provided by the present invention contains a rigid alicyclic structure, thereby imparting excellent heat resistance to the resin.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A low dielectric, high heat-resistant adamantane-type maleimide resin, the general chemical structure of which is shown in (I):
[0010]
[0011] The low dielectric and heat-resistant adamantane-type maleimide resin provided by the present invention is a brown or yellow solid with an acid value of
[0012] ≤2.0mg(KOH) / g, softening point 70~100℃.
[0013] In addition, to achieve the above-mentioned object, the present invention also provides a method for preparing a low-dielectric, high-heat-resistant adamantane-type maleimide resin, comprising the following steps:
[0014] S1, dissolving an adamantane-type amino compound in an organic solvent A to obtain a solution A;
[0015] Add maleic anhydride to a reaction flask equipped with a stirring device, a temperature control device, and a reflux device, then add organic solvent B and stir to dissolve the maleic anhydride to obtain solution B;
[0016] S2, adding the solution A to the solution B dropwise within 2 to 4 hours, and continuing to stir and react at 20 to 60° C. for 4 to 6 hours after the addition is complete;
[0017] S3, adding acetic anhydride and a catalyst to the solution after stirring the reaction in step S2, then heating to 90-110° C. and keeping the temperature for 4-6 hours;
[0018] S4, cooling the solution after the heat-insulating reaction in step S3, and then washing and removing the solvent to obtain a low-dielectric, high-heat-resistant adamantane-type maleimide resin.
[0019] The reaction mechanism of the low dielectric and heat-resistant adamantane maleimide resin of the present invention is as follows: the amino group on the adamantane amino compound reacts with maleic anhydride to form maleimide acid, which is further dehydrated into a ring under the action of a catalyst to form a maleimide group.
[0020] The low dielectric and heat-resistant adamantane maleimide resin of the present invention has good performance parameters, specifically: acid value
[0021] ≤2mg(KOH) / g, softening point 70~100℃.
[0022] As one of the embodiments of the present application, the adamantane-type amino compound has the chemical structure formula shown in (II):
[0023]
[0024]
[0025] The low-dielectric and heat-resistant adamantane-type maleimide resin is a brown or yellow solid, has an acid value of ≤2 mg (KOH) / g, and a softening point of 70-100°C.
[0026] As one possible embodiment of the present application, the molar ratio of the adamantane-type amino compound, maleic anhydride, acetic anhydride and the catalyst is 1: (1-1.4): (0.6-0.7): (0.05-0.07).
[0027] As one possible embodiment of the present application, in step S1, the organic solvent A and the organic solvent B are any one or more of toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.
[0028] As one possible embodiment of the present application, in step S3, the catalyst is any one or more of sodium acetate, nickel acetate, cobalt acetate, and magnesium acetate.
[0029] In addition, to achieve the above-mentioned purpose, the present invention also provides a use of a low-dielectric, high-heat-resistant adamantane-type maleimide resin in the preparation of a low-dielectric, high-performance copper-clad laminate. The preparation method of the low-dielectric, high-performance copper-clad laminate is as follows:
[0030] S1. Take 100 parts by mass of a low dielectric, high heat-resistant adamantane-type maleimide resin, 10 to 20 parts by mass of an unsaturated polyphenylene ether resin, 10 to 30 parts by mass of a cyanate ester resin, and 0.05% to 0.6% by mass of the total mass of the resin catalyst and 50% to 80% by mass of the total mass of the resin filler mixed; thereafter, an organic solvent C is added to configure a resin solution;
[0031] The total mass of the resin refers to the sum of the masses of the low dielectric and high heat-resistant adamantane-type maleimide resin, the unsaturated polyphenylene ether resin and the cyanate ester resin.
[0032] S2. The glass fiber cloth is immersed in the resin solution, and then the glass fiber cloth containing the resin solution is baked in an oven at 120 ℃ ~ 180 ℃ for 5min-15min to obtain a low dielectric resin prepreg;
[0033] S3. Overlapping the multilayer prepregs between the copper foils, placing them in a vacuum hot press for hot pressing, thereby obtaining the low-dielectric, high-performance copper-clad laminate.
[0034] As one possible embodiment of the present application, the unsaturated polyphenylene ether resin has the chemical structure formula shown in (IV):
[0035]
[0036] Here, n7 is any integer from 6 to 20.
[0037] As one of the possible embodiments of the present application, the cyanate ester resin is any one of bisphenol A cyanate ester resin (abbreviated as ACE), bisphenol E cyanate ester resin (abbreviated as ECE), novolac cyanate ester resin (abbreviated as PCE), and dicyclopentadiene bisphenol cyanate ester resin (abbreviated as DCPDCE).
[0038] As one possible embodiment of the present application, the initiator is any one of dicumyl peroxide, di-tert-butyl peroxide, and tert-butyl perbenzoate.
[0039] As one possible embodiment of the present application, the filler is spherical nanoparticles treated with a silane coupling agent, and the spherical nanoparticles are any one of silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, and barium sulfate.
[0040] As one of the possible embodiments of the present application, the organic solvent C is any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, and propylene glycol methyl ether acetate.
[0041] As one possible embodiment of the present application, the number of layers of the prepreg is 3 to 20.
[0042] As one possible embodiment of the present application, the fiberglass cloth model is any one of 1080E, 2116, 2313, 3313, and 7628.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] (1) The adamantane-type maleimide resin provided by the present invention contains a non-planar alicyclic structure that effectively disrupts the molecular regularity of bismaleimide resins, thereby resolving the poor solubility problem of conventional bismaleimide resins and significantly extending the processing window for maleimide resins in copper-clad laminate preparation. Furthermore, the structure contains only carbon and hydrogen, which imparts excellent dielectric properties to the resin.
[0045] (2) The adamantane maleimide resin provided by the present invention is used to prepare a low-dielectric, high-performance copper-clad laminate. The prepared copper-clad laminate has excellent comprehensive properties: glass transition temperature (Tg) 245-248°C (indicating that the copper-clad laminate of the present invention has high heat resistance), thermal delamination time T300 ≥ 60 min, dielectric constant Dk ≤ 2.58 under 10G conditions, dielectric loss Df ≤ 0.0027, and solder immersion resistance (with copper, 288°C) ≥ 300 s.
[0046] (3) The product of the present invention has a simple preparation process, is easy to operate, and has strong practicality. DETAILED DESCRIPTION
[0047] Part 1 Preparation of Low Dielectric, High Heat Resistant Adamantane Maleimide Resins (Examples 1-3)
[0048] Example 1
[0049] a. Add 1 mol of an amino compound containing an adamantane structure into a beaker and dissolve it in a mixture of xylene and NN-2-methylformamide (10:1).
[0050] b. Add 1.2 mol of maleic anhydride to a 5 L reaction flask equipped with a stirrer, temperature controller, and reflux system. Add a certain amount of a mixed solution of xylene and NN-2-methylformamide (15:1) and stir at room temperature to dissolve the maleic anhydride. Then, add the dissolved amino compound solution containing an adamantane structure dropwise to the reaction flask over 2.5 hours. After the addition is complete, continue stirring at 45°C for 4 hours.
[0051] c. Add 0.6 mol of acetic anhydride and 0.06 mol of catalyst, raise the temperature to 100°C and keep the temperature for 4 hours;
[0052] d. After the reaction is completed, the mixture is cooled to 70° C., washed with water (pure water, deionized water or distilled water) for multiple times, and then the solvent is removed by reduced pressure distillation to obtain a low dielectric, high heat-resistant adamantane-configured maleimide resin.
[0053] The results of the test showed that the prepared low dielectric and high heat-resistant adamantane-configured maleimide resin was clear and transparent in solubility in butanone (solid content 50 wt%), and had an acid value of 0.77 mgKOH / g.
[0054] Example 2
[0055] a. Add 1 mol of an amino compound containing an adamantane structure into a beaker and dissolve it in a mixture of xylene and NN-2-methylformamide (10:1).
[0056] b. Add 1.2 mol of maleic anhydride to a 5 L reaction flask equipped with a stirrer, temperature controller, and reflux system. Add a certain amount of a mixed solution of xylene and NN-2-methylformamide (15:1) and stir at room temperature to dissolve the maleic anhydride. Then, add the dissolved amino compound solution containing an adamantane structure dropwise to the reaction flask over 2.5 hours. After the addition is complete, continue stirring at 45°C for 4.5 hours.
[0057] c. Add 0.6 mol of acetic anhydride and 0.06 mol of catalyst, raise the temperature to 100°C and keep the temperature for 4.5 hours;
[0058] d. After the reaction is completed, the mixture is cooled to 70° C., washed with water (pure water, deionized water or distilled water) for multiple times, and then the solvent is removed by reduced pressure distillation to obtain a low-dielectric and high-heat-resistant adamantane-configuration maleimide resin.
[0059] The results of the test showed that the prepared low-dielectric and high-heat-resistant adamantane-configuration maleimide resin was clear and transparent in solubility in butanone (solid content 50 wt%), and had an acid value of 0.45 mgKOH / g.
[0060] Example 3
[0061] a. Add 1 mol of an amino compound containing an adamantane structure into a beaker and add a certain amount of a mixed solution of xylene and NN-2-methylformamide (10:1) to dissolve it.
[0062] b. Add 1.2 mol of maleic anhydride to a 5 L reaction flask equipped with a stirrer, temperature controller, and reflux system. Add a certain amount of a mixed solution of xylene and NN-2-methylformamide (15:1) and stir at room temperature to dissolve the maleic anhydride. Then, add the dissolved amino compound solution containing an adamantane structure dropwise to the reaction flask over 2.5 hours. After the addition is complete, continue stirring at 45°C for 5 hours.
[0063] c. Add 0.6 mol of acetic anhydride and 0.06 mol of catalyst, raise the temperature to 100°C and keep the temperature for 5 hours;
[0064] d. After the reaction is completed, the mixture is cooled to 70° C., washed with water (pure water, deionized water or distilled water) for multiple times, and then the solvent is removed by distillation under reduced pressure to obtain a low-dielectric maleimide resin containing adamantane configuration.
[0065] The results of the test showed that the prepared low-dielectric and high-heat-resistant adamantane-configured maleimide resin was clear and transparent in solubility in butanone (solid content 50 wt%), and had an acid value of 0.75 mgKOH / g.
[0066] Part II Preparation of Low Dielectric and High Performance Copper Clad Laminates (Examples 4-7)
[0067] S1. Take 100 parts by mass of the low dielectric, heat-resistant adamantane-type maleimide resin prepared in Example 1-3, 10 to 20 parts by mass of unsaturated polyphenylene ether resin, 10 to 30 parts by mass of cyanate ester resin, and 0.05% to 0.6% of the total mass of the resin (the sum of the masses of the above three resins, the same below) of the catalyst and 50% to 80% of the total mass of the resin. Mix them, and add an appropriate amount of organic solvent B to prepare a resin solution with a solid content of 65% (the above non-volatile matter accounts for 65% of the total mass).
[0068] S2. Immerse the glass fiber cloth in the resin solution, and then bake the glass fiber cloth containing the resin solution in an oven at 120° C. to 180° C. for 5 min to 15 min to prepare a low dielectric resin prepreg.
[0069] S3. Overlap an appropriate number of prepregs between copper foils and place them in a vacuum hot press. Raise the temperature from room temperature to 175°C at a rate of 3°C / min, and increase the pressure from 0.5MPa to 4MPa at a rate of 0.1MPa / 1min. Evacuate to less than 50torr and keep pressing for 1-2h. Then raise the temperature to 200-240°C and keep constant pressure for 3-5h. Release the pressure and cool naturally to obtain a low-dielectric, high-performance copper clad laminate.
[0070] Comparative Example 1
[0071] S1. Take 100 parts by mass of bismaleimidodiphenylmethane (BMI), 15 parts by mass of unsaturated polyphenylene ether resin SA9000, 25 parts by mass of bisphenol A cyanate resin, and 0.56 parts by mass of diisostyrene oxide and 85 parts by mass of silica, the total mass of the resin (the sum of the masses of the above three resins, the same below), and add 122 parts by mass of butanone to prepare a resin solution with a solid content of 65% (the mass of the above non-volatile matter accounts for 65% of the total mass).
[0072] S2. Immerse the glass fiber cloth in the resin solution, and then bake the glass fiber cloth containing the resin solution in an oven at 120° C. to 180° C. for 5 min to 15 min to prepare a low dielectric resin prepreg.
[0073] S3. Overlap an appropriate number of prepregs between copper foils, place them in a vacuum hot press, raise the temperature from room temperature to 175°C at a heating rate of 3°C / min, increase the pressure from 0.5 MPa to 4 MPa at a rate of 0.1 MPa / 1 min, evacuate to less than 50 torr, maintain pressing for 1 to 2 hours, then raise the temperature to 200 to 240°C and maintain constant pressure for 3 to 5 hours, release the pressure and cool naturally to obtain the copper clad laminate of Comparative Example 1.
[0074] Comparative Example 2
[0075] S1. Take 100 parts by mass of indane maleimide (indane BMI), 15 parts by mass of unsaturated polyphenylene ether resin SA9000, 25 parts by mass of bisphenol A cyanate resin, and 0.56 parts by mass of diisostyrene oxide and 85 parts by mass of silica, the total mass of the resin (the sum of the masses of the above three resins, the same below), and add 122 parts by mass of butanone to prepare a resin solution with a solid content of 65% (the above non-volatile matter mass accounts for 65% of the total mass).
[0076] S2. Immerse the glass fiber cloth in the resin solution, and then bake the glass fiber cloth containing the resin solution in an oven at 120° C. to 180° C. for 5 min to 15 min to prepare a low dielectric resin prepreg.
[0077] S3. Overlap an appropriate number of prepregs between copper foils, place them in a vacuum hot press, raise the temperature from room temperature to 175°C at a heating rate of 3°C / min, increase the pressure from 0.5 MPa to 4 MPa at a rate of 0.1 MPa / 1 min, evacuate to less than 50 torr, maintain pressing for 1 to 2 hours, then raise the temperature to 200 to 240°C and maintain constant pressure for 3 to 5 hours, release the pressure and cool naturally to obtain the copper clad laminate of Comparative Example 2.
[0078] Table 1 shows the proportions and performance parameters of the raw material components in the method for preparing low-dielectric, high-performance copper-clad laminates using low-dielectric, heat-resistant adamantane-type maleimide resin in Examples 4 to 7, as well as the relevant performance parameters of the copper-clad laminates prepared in Examples 4-7 and Comparative Examples 1-2.
[0079] In Table 1, the units of component amounts are parts by mass.
[0080] A1 is: the low dielectric, heat-resistant adamantane-type maleimide resin prepared in Example 1;
[0081] A2 is: the low dielectric, heat-resistant adamantane-type maleimide resin prepared in Example 2;
[0082] A3 is: the low dielectric, heat-resistant adamantane-type maleimide resin prepared in Example 3;
[0083] B is: bisphenol A cyanate ester resin, Yangzhou Tianqi New Materials Co., Ltd.
[0084] C is: unsaturated polyphenylene ether resin SA9000, Saudi Basic Industries Corporation;
[0085] D is: dicumyl peroxide, Hongbaoli Group Co., Ltd.;
[0086] E is silicon dioxide, produced by Jiangsu Lianrui DQ1040;
[0087] F is: butanone.
[0088] In addition, the relevant standards used for the technical indicators in Table 1 are as follows:
[0089] Glass transition temperature Tg: measured by dynamic mechanical analysis (DMA) according to the DMA method specified in 2.4.24.4 of IPC-TM-650;
[0090] Dielectric constant Dk and dielectric loss Df: Use the SPDR method to test 10GHz data according to the method specified in IEC 61189-2-721;
[0091] Thermal delamination time T300: measured according to the method specified in 2.4.24.1 of IPC-TM-650;
[0092] Solder immersion time with copper foil: Take plate samples with a size of 100mm×100mm and copper foil on both sides, immerse them in 288℃ solder respectively, and take the average time without delamination and cracking.
[0093] Table 1:
[0094]
[0095]
[0096] As shown in Table 1, the low-dielectric, high-performance copper-clad laminate prepared by the present invention has good performance, specifically:
[0097] The glass transition temperature (Tg) is 245-248°C (indicating that the copper-clad laminate of the present invention has high heat resistance), the thermal delamination time T300 is ≥60 minutes, the dielectric constant Dk is ≤2.58 under 10G conditions, the dielectric loss Df is ≤0.0027, and the solder dip resistance (with copper, 288°C) is ≥300 seconds. Compared with Comparative Examples 1 and 2, its dielectric constant and dielectric loss are significantly reduced.
Claims
1. A low dielectric, high heat-resistant adamantane-type maleimide resin, characterized in that: Its chemical structure is shown in the formula (Ⅰ):
2. The method for preparing a low dielectric and high heat-resistant adamantane-type maleimide resin according to claim 1, characterized in that: The steps include: S1, dissolving an adamantane-type amino compound in an organic solvent A to obtain a solution A; Add maleic anhydride to a reaction flask equipped with a stirring device, a temperature control device, and a reflux device, then add organic solvent B and stir to dissolve the maleic anhydride to obtain solution B; S2, adding the solution A to the solution B dropwise within 2 to 4 hours, and continuing to stir and react at 20 to 60° C. for 4 to 6 hours after the addition is complete; S3, adding acetic anhydride and a catalyst to the solution after stirring the reaction in step S2, then heating to 90-110° C. and keeping the temperature for 4-6 hours; S4, cooling the solution after the heat-insulating reaction in step S3, and then washing and removing the solvent to obtain a low-dielectric, high-heat-resistant adamantane-type maleimide resin.
3. The method for preparing a low dielectric and high heat-resistant adamantane-type maleimide resin according to claim 2, characterized in that: The adamantane-type amino compound has the chemical structural formula shown in (II):
4. The method for preparing a low dielectric and high heat-resistant adamantane-type maleimide resin according to claim 2, characterized in that: The molar ratio of the adamantane-type amino compound, maleic anhydride, acetic anhydride and the catalyst is 1:(1-1.4):(0.6-0.7):(0.05-0.07).
5. The method for preparing a low dielectric and high heat-resistant adamantane-type maleimide resin according to claim 2, characterized in that: In step S3, the catalyst is any one or more of sodium acetate, nickel acetate, cobalt acetate, and magnesium acetate.
6. Use of the low dielectric and high heat-resistant adamantane-type maleimide resin according to claim 1 in preparing a low dielectric and high-performance copper-clad laminate, characterized in that: The preparation method of the low dielectric high performance copper clad laminate is as follows: S1. Take 100 parts by mass of a low dielectric, high heat-resistant adamantane-type maleimide resin, 10 to 20 parts by mass of an unsaturated polyphenylene ether resin, 10 to 30 parts by mass of a cyanate ester resin and 0.05% to 0.6% of the total mass of the resin catalyst and 50% to 80% of the total mass of the resin filler mixed; thereafter, an organic solvent C is added to configure a resin solution; The total mass of the resin refers to the sum of the masses of the low dielectric, high heat-resistant adamantane-type maleimide resin, the unsaturated polyphenylene ether resin and the cyanate ester resin; S2. The glass fiber cloth is immersed in the resin solution, and then the glass fiber cloth containing the resin solution is baked in an oven at 120 ℃ ~ 180 ℃ for 5min-15min to obtain a low dielectric resin prepreg; S3. Overlapping the multilayer prepregs between the copper foils, placing them in a vacuum hot press for hot pressing, thereby obtaining the low-dielectric, high-performance copper-clad laminate.
7. Use of the low dielectric and high heat-resistant adamantane-type maleimide resin according to claim 6 in preparing a low dielectric and high performance copper clad laminate, characterized in that: The unsaturated polyphenylene ether resin has the general chemical structure formula shown in (IV): Here, n7 is an arbitrary integer from 6 to 20.
8. Use of the low dielectric and high heat resistant adamantane-type maleimide resin according to claim 6 in preparing a low dielectric and high performance copper clad laminate, characterized in that: The cyanate resin is any one of bisphenol A cyanate resin, bisphenol E cyanate resin, novolac cyanate resin, and dicyclopentadiene bisphenol cyanate resin. The initiator may be any one of dicumyl peroxide, di-tert-butyl peroxide, and tert-butyl perbenzoate.
9. Use of the low dielectric and high heat-resistant adamantane-type maleimide resin according to claim 6 in preparing a low dielectric and high-performance copper-clad laminate, characterized in that: The filler is spherical nanoparticles treated with a silane coupling agent, and the spherical nanoparticles are any one of silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, and barium sulfate.
Citation Information
Patent Citations
Low-dielectric and high-toughness indane condensed-configuration maleimide resin as well as preparation method and application thereof
CN117946394A
Cited By
Bismaleimide-silane modified adhesive and preparation method thereof
CN121801499A